2010
DOI: 10.1136/jme.2009.032862
|View full text |Cite
|
Sign up to set email alerts
|

One step forward, two steps back? The GMC, the common law and ‘informed’ consent

Abstract: Until 2008, if doctors followed the General Medical Council's (GMC's) guidance on providing information prior to obtaining a patient's consent to treatment, they would be going beyond what was technically required by the law. It was hoped that the common law would catch up with this guidance and encourage respect for patients' autonomy by facilitating informed decision-making. Regrettably, this has not occurred. For once, the law's inability to keep up with changing medical practice and standards is not the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Participants’ perceptions reflect the paternalism of the reasonable doctor standard, where the doctor speaks and the patient listens (Fovargue and Miola, 2010). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants’ perceptions reflect the paternalism of the reasonable doctor standard, where the doctor speaks and the patient listens (Fovargue and Miola, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…In a study involving cancer patients in Canada, Sinding et al (2010) found that patients were uncomfortable with what they perceived as an expectation that they were responsible for making decisions about their treatment. When patients are left to decide on the type of treatment, they may feel unsupported through having to make decisions based on information that they might not fully understand (Fovargue and Miola, 2010; Sinding et al, 2010). This supports an argument that requirements to provide patients with more information are being conflated with the informed model, that is where the patient makes the decision, rather than the shared decision-making model (Charles et al, 1999; Fovargue and Miola, 2010; Jones, 1999).…”
Section: Consent To Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only must the patient receive the information typically imparted to those due to undergo the procedure, he or she should also obtain information specific to the circumstances of live broadcast. 7 Of undoubted importance here will be information about any risks attending the presence of the cameras and any other unusual features. Instructions and requests from the director of the broadcast, the camera operators and even members of the audience (such as via Twitter, in the case of the Channel 4 programme) might all be expected to exert some influence on how the procedure is conducted.…”
Section: Respecting the Patient's Autonomy?mentioning
confidence: 99%
“…Professional regulatory bodies, such as the General Medical Council, 5 endorse the subjective standard, and it can be argued that such guidance mandates the practice of a 'reasonable' surgeon. 6 In reality, a subjective standard not only creates enormous practical challenges but also may expose surgeons unfairly to the hindsight of dissatisfied patients. Indeed, some eminent bioethicists agree that it imposes unfairly burdensome and unachievable requirements.…”
mentioning
confidence: 99%